The Paradigm of Ki Hadjar Dewantara's Drama on Education Through Art - hari pramono, koko; sabri, indar; Haldini Muhammad , Anbie (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
Questioning the development of theater in Indonesia is certainly still an interesting topic in a research. This is often experienced by a theater activist or researcher who specifically focuses on the field of theater art. The development of modern theater art began to develop in Indonesia in 1926 with the free-to-air script by Rustam Efendi. However, there are interesting and unrevealed things about Ki Hadjar Dewantara's work with the concept of play as a performing art that has its own paradigm. Therefore, this study will focus on the paradigm of Ki Hadjar Dewantara's play with the use of literature study research to reveal the results of research which will later be used as a literature reference for past data about plays.